Penecontemporaneous deformation in the Nyalau Formation (Oligo-Miocene), Central Sarawak - MAZLAN MADON, Mazlan (Geological Society of Malaysia, 2007)
Abstract: In the Nyalau Formation (Late Oligocene to Early Miocene in age) exposed near Tg. Similajau and Bintulu areas, structural features indicate that penecotemporaneous deformation is common. These features include (1) “disharmonic” thrusts and associated folding within shaly intervals, (2) detached normal and reverse faults within mud-dominated intervals, (3) subtle stratal termination and onlap patterns associated with faulting, folding and (probably subaquaeous) erosion of the sedimentary layers, (4) slump and load structures within lower shoreface to offshore-transition successions. These characteristics may be a common feature in deforming foreland basins, and indicate the importance of tectonic over eustatic controls on sedimentation and sequence development in the Tertiary NW Borneo basins.